Penerapan Analisis SWOT dalam Mewujudkan Ekowisata Mangrove yang Berkelanjutan - Dinda Nasya Atin; Yesi Kumalasari (GEMILANG: Jurnal Manajemen dan Akuntansi, 2022)
Mangrove ecotourism is a form of tourism that aims to preserve mangrove ecosystems while providing economic benefits to local communities. However, to ensure that this ecotourism can develop sustainably, there needs to be a systematic approach in its planning and management. The application of SWOT Analysis (Strengths, Weaknesses, Opportunities, Threats) is an effective method to evaluate various aspects of mangrove ecotourism. This study aims to explore the application of SWOT Analysis in designing strategies to realize sustainable mangrove ecotourism. By analyzing the strengths, weaknesses, opportunities, and threats associated with mangrove ecotourism, this study aims to identify strategies that can improve the sustainability and effectiveness of mangrove ecotourism. The results of this study indicate that SWOT analysis can provide deep insight into the internal and external factors affecting mangrove ecotourism development and assist in formulating appropriate strategies to achieve sustainability goals. The findings provide valuable guidance for more effective planning and management of mangrove ecotourism.